A survey on the knowledge, aspects and attitude of radiologists and radiology residents in Greece and Cyprus about the use of Artificial Intelligence in Radiology - Letsiou, Eleni; Konstantinidis, Theocharis; Sarafis, Pavlos; Saridi, Maria (International Conference on Business and Economics - Hellenic Open University, 2025)
Artificial intelligence is defined as the ability of machines to perform tasks that require human intelligence, and its application in Radiology has shown over the years promising enhancements in diagnostic and therapeutic capabilities. The aim of the research was to study the opinions and attitudes of Radiologists, both residents and specialists, in Greece and Cyprus. The research conducted in Greece and Cyprus includes the participation of 102 radiologists. Data were collected through a 36-question questionnaire, distributed between January 2024 and April 2024. Data were statistically analyzed using IBM SPSS Statistics, focusing on exploring primary and secondary variables related to the research. The study found that radiologists in Greece and Cyprus generally have a positive attitude toward AI, with 91.2% believing it will improve radiology, though concerns about its role as a secondary analyst and potential job displacement persist. Additionally, younger radiologists and residents demonstrated higher AI knowledge, greater willingness to undergo AI training, and a stronger inclination to integrate AI into clinical practice compared to their older and specialized counterparts. The results of the research highlight a correspondence of opinions, knowledge, and attitudes of Radiologists in Greece and Cyprus with corresponding international data. Therefore, the final integration of AI into clinical practice will depend on targeted education, regulatory clarity, and collaboration between radiologists and AI developers to address existing concerns and barriers. JEL Classification: I10 Keywords: Artificial Intelligence, Medical Imaging, Radiologists, Radiology